Determinación de los costos de fabricación de vino artesanal Santa Solera S.A.S, mediante la metodología de costos por procesos. (2020)
The present research work entitled: Determination of the Costs of Manufacture of Craft Wine Santa Solera SAS, by means of the process cost methodology, aims to identify the costs of winemaking, located in the Santa Elena region, as a decision-making tool. The type of research carried out was descriptive, since it focuses on highlighting the characteristics, observing and describing the behavior, for this, questions and data analyzes are carried out that are carried out on the artisanal wine company Santa Solera SAS, on the other On the other hand, this type of research offers more accurate and concise data and thus get to know the possible situations that arise in the company under investigation, and it is expected that when analyzing the variables the errors that occur in the company are found and give a solution to these. In conclusion, it can be analyzed as cost accounting, it is essential for the analysis of the company's processes, it not only analyzes the costs of the products and how they accumulate, but also helps to find improvement points so that the company has a better profitability.